1999
DOI: 10.1111/j.1741-6248.1999.00269.x
|View full text |Cite
|
Sign up to set email alerts
|

The Decision to Outsource Child Care in Households Engaged in a Family Business

Abstract: This research examines whether employment in a family‐owned business offers parents of young children more flexibility in balancing work and child care responsibilities than employment in nonfamily business situations. Specifically, the study focuses on whether the family business characteristics and work demands of household managers in these families explain the purchase of child care services in the market. The study uses a subsample from the 1997 National Family Business Survey (1997 NFBS). Findings sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Blanco-Mazagatos et al 2007state that family-owned firms manage their financial resources more efficiently than non-family owned firms due to ownership and management being more frequently in the same hands. Greater management flexibility in family-owned firms (Haynes, Avery, & Hunts, 1999;Thomas, 2009) can contribute decisively to family-owned firms making financing decisions with the goal of reaching their target long-term debt ratio. Firstly, the less constant need to resort to short-term debt, and consequently lesser need to renegotiate the terms of the short-term debt, can mean a slower speed of the adjustment of short-term debt towards target short-term debt ratio in familyowned firms, compared to what occurs in nonfamily owned firms.…”
Section: Sample Variables and Estimation Methods Samplementioning
confidence: 99%
“…Blanco-Mazagatos et al 2007state that family-owned firms manage their financial resources more efficiently than non-family owned firms due to ownership and management being more frequently in the same hands. Greater management flexibility in family-owned firms (Haynes, Avery, & Hunts, 1999;Thomas, 2009) can contribute decisively to family-owned firms making financing decisions with the goal of reaching their target long-term debt ratio. Firstly, the less constant need to resort to short-term debt, and consequently lesser need to renegotiate the terms of the short-term debt, can mean a slower speed of the adjustment of short-term debt towards target short-term debt ratio in familyowned firms, compared to what occurs in nonfamily owned firms.…”
Section: Sample Variables and Estimation Methods Samplementioning
confidence: 99%
“…It is also noteworthy that spouses who work together in (and possibly own together) an FB differ with respect to managing household responsibilities from spouses in the general WFI who are just dual earners. For instance, household managers with an FB are less likely to outsource their child care than their counterparts who work outside the FB (Haynes et al, 1999).…”
Section: Review Of the Fb Wfi Literaturementioning
confidence: 99%
“…Findings on family-friendly policies for family employees have been mixed. Some studies find that family members in FBs have more flexibility regarding child care (Avery et al, 2000; Haynes et al, 1999). However, Day (2013) observed that even though first-generation founders may create a family-friendly business culture, this does not necessarily extend to those FB-owning women who are mothers.…”
Section: Review Of the Fb Wfi Literaturementioning
confidence: 99%
“…The women in the study also had a positive view about their careers. Women's access to sectors traditionally regarded as 'masculine', for example the construction industry, have also been made possible by advantages, such as the introduction of flexible schedules, which some authors assert allow women to combine their professional responsibilities with child care (Dumas, 1992(Dumas, , 1998Frishkoff & Brown, 1993;Haynes, Avery & Hunts, 1999;Lyman et al, 1985).…”
Section: Gender Theory In Family Business Researchmentioning
confidence: 99%